2014
DOI: 10.1260/2041-4196.5.3.253
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of Blast Loading and Clearing on Small Targets

Abstract: When a blast wave strikes a finite target, diffraction of the blast wave around the free edge causes a rarefaction clearing wave to propagate along the loaded face and relieve the pressure acting at any point it passes over. For small targets, the time taken for this clearing wave to traverse the loaded face will be small in relation to the duration of loading.Previous studies have not shown what happens in the late-time stages of clearing relief, nor the mechanism by which the cleared reflected pressure decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 18 publications
(34 reference statements)
4
43
0
Order By: Relevance
“…However, in Figure 3 it is possible to support that the impulses could be estimated with confidence, knowing that ProsAir overestimates the impulse and LS-DYNA underestimates it. These results are in accordance with others in terms of LS-DYNA and Air3D (similar to ProsAir) behavior (Huang et al, 2012;Rigby et al, 2014;Trajkovski et al, 2014). Figure 1).…”
Section: Source: Authorssupporting
confidence: 92%
See 1 more Smart Citation
“…However, in Figure 3 it is possible to support that the impulses could be estimated with confidence, knowing that ProsAir overestimates the impulse and LS-DYNA underestimates it. These results are in accordance with others in terms of LS-DYNA and Air3D (similar to ProsAir) behavior (Huang et al, 2012;Rigby et al, 2014;Trajkovski et al, 2014). Figure 1).…”
Section: Source: Authorssupporting
confidence: 92%
“…As the data is required by volume, knowing the TNT equivalent and the density of the TNT introduced into the model (Table 1), the explosive volume (m 3 ) was calculated. The chosen meshing technique was the butterfly one, in order to ensure the good spherical shape of the shock wave as other authors suggest (Lapoujade et al, 2010 andRigby et al, 2014). The necessary data for the EOS used in this case, the traditional Jones-Wilkins-Lee (Lee et al, 1973), are shown in Table 1.…”
Section: Ls-dyna Modelling Processmentioning
confidence: 99%
“…A 100 mm thick steel target plate is underslung from the soffits of the horizontal beams and acts as a nominally rigid boundary to reflect the shock wave and detonation products impinging on the target after detonation of an explosive some distance beneath the centre of the plate. The plate is 1.4 m in diameter to negate the effect of blast wave clearing around the target edge [47].…”
Section: Experimental Setup 'Characterisation Of Blast Loading' Apparmentioning
confidence: 99%
“…Hence for these tests the clearing effects would have ceased relatively early on during the positive phase and no 'overshoot' early negative pressures would have been observed. This has recently been investigated by Rigby, Tyas, Bennett, Fay, Clarke & Warren (2014), where a series of numerical analyses were conducted to evaluate the cleared pressure-time history acting on rigid targets of decreasing size. The work showed that if the target was ∼250 times smaller than the distance from the blast to the target, then the clearing predictions could be reasonably well predicted by the Norris methodology.…”
Section: Literature Clearing Predictionsmentioning
confidence: 99%